Pelatihan Pembuatan Sabun Cuci Piring untuk Menambah Pendapatan Masyarakat Desa Kuala Terusan Riau - Oktavia, Al Putri; Ulfiana, Liza (Pakis Journal Institute, 2025)
This community service activity was carried out in Kuala Terusan Village, Pangkalan Kerinci Regency, with the aim of increasing the income of the Kuala Terusan Village community, specifically helping mothers with the idea of producing dishwashing soap to supplement household income. This training was motivated by the economic conditions of the community, which still relies on fishing for a livelihood, and is estimated to still require additional sources of income. The method of this activity included socialization and practical training on making liquid dishwashing soap, as well as assistance with soap packaging. The results of this activity showed that the community was enthusiastic about the information provided on how to increase income by producing dishwashing soap, and the community also understood the process of making dishwashing soap. This activity not only provided new skills but also fostered an entrepreneurial spirit and awareness of the importance of creativity in increasing household income.